A imunidade tributária das entidades do terceiro setor - Pimentel, Paulo Schmidt (2018)
This work has as its object the analysis of the tax immunity granted to non-profit social assistance institutions, provided by article 150, section VI, letter "c" and article 195, seventh paragraph, both of the Federal Constitution of 1988, which given the growing relevance of the third sector in our society, it is increasingly becoming the focus of legal discussions. In this sense, brief lines are presented of the formation of the State and, consequently, on its taxation power, in order to demonstrate the origin and functioning of the Brazilian constitutional tax system. It is then discussed on the granting of taxation power to federal entities and the constitutional limitations on the taxation power, to enable the demonstration of the tax immunities functioning in the legal system. With this, we proceed to the study of immunities in general, portraying their legal foundations, their presence and evolution in the constitutions already existing in our country and the academic classifications. With these notes, which are fundamental for the study of the tax immunity of social assistance institutions, the third sector is described and its importance in the so-called New Democratic State of Law. The entities of the third sector, described in the Federal Constitution as welfare institutions or social assistance institutions, have some characteristics, among them the provision of complementary services to the basic services of the State to the population and the lack of profit-making. Possessing such characteristics, Article 150, item VI, letter "c" of the Constitution still requires the fulfillment of other requirements to enable the use of the tax immunity. The controversy surrounding the nature of the law establishing these requirements, as well as the requirements provided by Article 14 of the National Tax Code are explained in detail. Finally, it analyzes the taxes reached by such immunity, even from the perspective of the Brazilian Courts